Transvaginal cholecystectomy vs conventional laparoscopic cholecystectomy for gallbladder disease: A meta-analysis - Xu, Bin (World J Gastroenterol, 2015)
AIM: To compare the results of transvaginal cholecystectomy (TVC) and conventional laparoscopic cholecystectomy (CLC) for gallbladder disease. METHODS: We performed a literature search of PubMed, EMBASE, Ovid, Web of Science, Cochrane Library, Google Scholar, MetaRegister of Controlled Trials, Chinese Medical Journal database and Wanfang Data for trials comparing outcomes between TVC and CLC. Data were extracted by two authors. Mean difference (MD), standardized mean difference (SMD), odds ratios and risk rate with 95%CIs were calculated using fixed- or random-effects models. Statistical heterogeneity was evaluated with the χ(2) test. The fixed-effects model was used in the absence of statistically significant heterogeneity. The random-effects model was chosen when heterogeneity was found. RESULTS: There were 730 patients in nine controlled clinical trials. No significant difference was found regarding demographic characteristics (P > 0.5), including anesthetic risk score, age, body mass index, and abdominal surgical history between the TVC and CLC groups. Both groups had similar mortality, morbidity, and return to work after surgery. Patients in the TVC group had a lower pain score on postoperative day 1 (SMD: -0.957, 95%CI: -1.488 to -0.426, P < 0.001), needed less postoperative analgesic medication (SMD: -0.574, 95%CI: -0.807 to -0.341, P < 0.001) and stayed for a shorter time in hospital (MD: -1.004 d, 95%CI: -1.779 to 0.228, P = 0.011), but had longer operative time (MD: 17.307 min, 95%CI: 6.789 to 27.826, P = 0.001). TVC had no significant influence on postoperative sexual function and quality of life. Better cosmetic results and satisfaction were achieved in the TVC group. CONCLUSION: TVC is safe and effective for gallbladder disease. However, vaginal injury might occur, and further trials are needed to compare TVC with CLC.